TSF radio live - the journalistic coverage of the Chiado fire in Lisbon (1988) - Luís Bonixe (Historia y Comunicación Social, 2021)
On 25 August 1988, a fire broke out in the Chiado area of Lisbon. It is considered one of the biggest fires in an urban area in Portugal, having destroyed a vast built historical heritage and caused several victims. The Portuguese news radio, TSF, was the first media outlet to report the news by starting a long special live emission putting into practice an innovative model of radio journalism for that time in Portugal which was based on the priority given to live informative reporting. The experience of this long live report was replicated in the following years by TSF in the coverage of other events. In this article, we analyse TSF's live coverage of the fire and reflect on the role of this experience in the journalistic model implemented by the radio in the following years.